Modelling urban growth: a prospective population, housing and job location model - Carlos Marmolejo Duarte; Manuel Ruiz Lineros; Jorge Cerda Troncoso; Josep Roca Cladera; Jaume Masip Tresserra (European Regional Science Association (ERSA), 2011)
Demographic projections have become in a useful tool in the planning of urban land provision. In the context of a more comprehensive research orientated towards the construction of a system to evaluate the impact of new infrastructure and urban projects on the efficiency of metropolis (i.e. in terms of mobility and environmental sustenaibility) a prospective urban growth model has been built-in. In this paper such a model is exposed. The model simulates the natural movement of population across the time and space, at the time that allows for migration according to the capacity of labor market to absorb new working migrants. The outputs suggest the total population, employment and housing demand in a spatial-temporal framework. Results for Catalonia and the Metropolitan Region of Barcelona illustrate the use of the model.
Keywords: 330